The Origin of Animal Multicellularity and Cell Differentiation - Brunet, Thibaut; King, Nicole (Developmental cell, 2017)
Over 600 million years ago, animals evolved from a unicellular or colonial organism whose cell(s) captured bacteria with a collar complex, a flagellum surrounded by a microvillar collar. Using principles from evolutionary cell biology, we reason that the transition to multicellularity required modification of pre-existing mechanisms for extracellular matrix synthesis and cytokinesis. We discuss two hypotheses for the origin of animal cell types: division of labor from ancient plurifunctional cells and conversion of temporally alternating phenotypes into spatially juxtaposed cell types. Mechanistic studies in diverse animals and their relatives promise to deepen our understanding of animal origins and cell biology. Brunet and King examine the origin of animal multicellularity. The authors suggest that changes in the mechanisms regulating extracellular matrix synthesis and cytokinesis may underlie the transition to multicellularity, and they propose two hypotheses to explain the evolution of cell differentiation in the animal lineage.